Evaluation Of Dengue Fever Knowledge Among The General Population And Its Prevalence, Clinical Features In Penang General Hospital - Wazir, Khurshid Alam (2000)

(untitled)
Dengue is one of the most important global public health problem, particularly in South East Asian countries. Despite the presence of the disease in Penang since 1902, no documented evidence existed on the knowledge of dengue among the general population. The current resurgence of the disease necessitates an evaluation of public knowledge, prevalence, clinical features and fluid management of dengue in Penang. In cross-sectional study data were collected from the general population to asses the knowledge. A total of 862 respondents of the population were participated in the study.Majority (97.2%) of the population were familiar with the disease dengue.